Challenge of transport telematics : 16th International Conference on Transport Systems Telematics, TST 2016, Katowice-Ustroń, Poland, March 16-19, 2016, Selected papers /: 16th International Conference on Transport Systems Telematics, TST 2016, Katowice-Ustroń, Poland, March 16-19, 2016, Selected papers. (2016) - Unknown
No abstract available